2015
DOI: 10.1111/1462-2920.13078
|View full text |Cite
|
Sign up to set email alerts
|

Copper homeostasis at the host vibrio interface: lessons from intracellular vibrio transcriptomics

Abstract: Recent studies revealed that several vibrio species have evolved the capacity to survive inside host cells. However, it is still often ignored if intracellular stages are required for pathogenicity. Virulence of Vibrio tasmaniensis LGP32, a strain pathogenic for Crassostrea gigas oysters, depends on entry into hemocytes, the oyster immune cells. We investigated here the mechanisms of LGP32 intracellular survival and their consequences on the host-pathogen interaction. Entry and survival inside hemocytes were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 43 publications
4
36
0
Order By: Relevance
“…parahaemolyticus invasion (Figure ). Given that (a) increasing findings have shown that host cells entry by some Vibrio species is related to their pathogenicity (Duperthuy et al, ; Pajuelo, Lee, Roig, Hor, & Amaro, ; Rosenberg & Falkovitz, ; Vanhove et al, ), (b) MAM7 and VpadF are required for in vivo bacterial virulence (Krachler et al, ; Liu & Chen, ), and (c) type I collagen and α1β1 integrin are abundant in the small intestine (Lussier et al, ; Tulli et al, ), it is probable that the invasion of host cells is an important pathogenic process for V . parahaemolyticus .…”
Section: Discussionmentioning
confidence: 99%
“…parahaemolyticus invasion (Figure ). Given that (a) increasing findings have shown that host cells entry by some Vibrio species is related to their pathogenicity (Duperthuy et al, ; Pajuelo, Lee, Roig, Hor, & Amaro, ; Rosenberg & Falkovitz, ; Vanhove et al, ), (b) MAM7 and VpadF are required for in vivo bacterial virulence (Krachler et al, ; Liu & Chen, ), and (c) type I collagen and α1β1 integrin are abundant in the small intestine (Lussier et al, ; Tulli et al, ), it is probable that the invasion of host cells is an important pathogenic process for V . parahaemolyticus .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transcriptomics by RNA sequencing was investigated regarding intracellular survival mechanism of Vibrio tasmaniensis (LGP32) and its interactions with C. gigas haemocytes (Vanhove et al . ). A profound boost in metabolic activity and a major transcription of antioxidant and copper detoxification genes was observed in LGP32 intracellular stages, suggesting the key role of copper efflux and antioxidants in Vibrio survival inside host cells (Vanhove et al .…”
Section: Applications Of Genomics and Transcriptomics In C Gigas Mormentioning
confidence: 97%
“…A profound boost in metabolic activity and a major transcription of antioxidant and copper detoxification genes was observed in LGP32 intracellular stages, suggesting the key role of copper efflux and antioxidants in Vibrio survival inside host cells (Vanhove et al . ).…”
Section: Applications Of Genomics and Transcriptomics In C Gigas Mormentioning
confidence: 97%
“…For example virulent populations of V. tasmaniensis and V. crassostreae , have been positively associated to diseased oysters and found to co‐occur at the individual level. Infection with V. tasmaniensis involves an intracellular phase in hemocytes and resistance to antimicrobial peptides, reactive oxygen species and copper (Duperthuy et al ., , Vanhove et al ., ). Infection with V. crassostreae relies at least partially on distinct genes encoding for unknown functions (Bruto et al ., ; Lemire et al ., ).…”
Section: Hey Molecular Biologist ‘Take a Walk On The Wild Side’ Lou Rmentioning
confidence: 97%